Understanding the role of unstructured socializing with peers and peer delinquency as mediators in the relationship of parental monitoring and delinquency - Archer, Robert (Journal of crime and justice, 2022)
In Osgood and colleagues (1996), theoretical formulation of unstructured socializing with peers (USWP), namely, the routine activity theory of general deviance posits that spending time in situations with friends, that lack structure, without authority figures present are more conducive to deviance. The present study advances understanding of this situation through use of an initial sample of over 3,500 adolescents from the Gang Resistance Education and Training (GREAT) program to examine whether the relationships between parental knowledge and delinquency/substance use are mediated by USWP and peer delinquency/peer substance use. Results showed that lack of parental knowledge leads to greater USWP, which then leads to peer delinquency/peer substance use to result in individual delinquency/substance use. By better understanding the various ways adolescents who spend time in settings of unstructured socializing with peers engage in delinquency, both parents and societal members can take steps to reduce these behaviors, which lead to deviant behavior